AWS certified cloud practitioner (CLF-C01). (LiveLessons (Indianapolis, Ind.), 2023)
8 Hours of Video Instruction 8 Hours of Video Instruction and Test-Taking Strategies for the AWS Certified Cloud Practitioner (CLF-C01) Exam Overview : The AWS Certified Cloud Practitioner (CLF-C01) Complete Video Course is your full resource to gaining a foundational understanding of AWS Cloud concepts, services, and terminology. It is also the key to successfully studying for your first AWS exam. The CLF-C01 exam is the first step in AWS certification. This 8-hour video training was designed to teach you the key concepts needed to pass the exam and learn practical skills. It focuses on each of the exam objectives and provides in-depth quiz question breakdowns throughout so you can see in real-time how to approach and answer exam questions. Best-selling author and trainer Chad Smith will share his extensive knowledge of the AWS Certified Cloud Practitioner materials, so you are prepared and confident on exam day. AWS Certifications are among the most sought-after in the Technology sector, and the certification exams cover a wide range of services, technologies, and implementation patterns. Topic included in this course: Exam Foundation introduces the Cloud Practitioner exam material and set the stage for the rest of the course content. Includes exam registration process, exam question format, and covers some general answer strategies with a focus on time management. Cloud Concepts covers the basics of cloud terminology. Includes introductory concepts for cloud economics and the principles of being "Well-Architected." This module goes in deep about AWS Well-Architected Framework and its six pillars. Security and Compliance covers larger security topics like Business Continuity and Disaster Recovery and network security implementation via Security Groups. Core AWS Services teaches methods of API endpoints that can be used for deploying and operating AWS services and resources. Billing and Pricing teaches the common exam scenario for pricing models, EC2 pricing by covering multiple account strategies and deep diving into the billing support resources is also included. Next Steps focuses on the next steps you can take to further your understanding of Solutions Architecture in AWS. About the Instructor Chad Smith is a technology professional who is focused on cloud infrastructure and management. He is the Principal Cloud Architect at Brightkey.cloud. He brings a wealth of personal real-world experience in cloud adoption, infrastructure design, operations and security. He holds current AWS certifications in Architecture, SysOps, Security, Networking and Databases and is also certified in CompTIA Cloud+. Skill Level : Beginner Learn How To : Prepare for the CLF-C01 exam Compute the EC2 service available in AWS Understand the basics of cloud terminology including Cloud Economics, Cloud Architecture Design Principle Understand Cloud Value Proposition and Cloud Business Value Understand the importance of Cloud Security Understand different cloud deployment patterns Solve customer-needed assistance with the deployment or operation of a core infrastructure service Course Requirements: N/A Who Should Take This Course : Cloud beginners AWS beginners Project managers Anyone wanting to start their AWS certification journey About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.